Predicting MAOD Using Only a Supramaximal Exhaustive Test - Bertuzzi, R. C. M.; Franchini, E.; Ugrinowitsch, C.; Kokubun, Eduardo [UNESP]; Lima-Silva, A. E.; Pires, F. O.; Nakamura, F. Y.; Kiss, M. A. P. D. M. [UNESP] (Georg Thieme Verlag Kg, 2010)
The objective of this study was to propose an alternative method (MAOD(ALT)) to estimate the maximal accumulated oxygen deficit (MAOD) using only one supramaximal exhaustive test. Nine participants performed the following tests: (a) a maximal incremental exercise test, (b) six submaximal constant workload tests, and (c) a supramaximal constant workload test. Traditional MAOD was determined by calculating the difference between predicted O(2) demand and accumulated O(2) uptake during the supramaximal test. MAOD(ALT) was established by summing the fast component of excess post-exercise oxygen consumption and the O(2) equivalent for energy provided by blood lactate accumulation, both of which were measured during the supramaximal test. There was no significant difference between MAOD (2.82 +/- 0.45 L) and MAOD(ALT) (2.77 +/- 0.37 L) (p = 0.60). The correlation between MAOD and MAOD(ALT) was also high (r = 0.78; p = 0.014). These data indicate that the MAOD(ALT) can be used to estimate the MAOD.
Keywords: oxygen uptake; blood lactate; excess post-exercise oxygen consumption